2021
DOI: 10.2147/jir.s316262
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Inflammatory and Oxidative Stress Biomarkers and Plasma Metabolites in a Longitudinal Study of Healthy Male Welders

Abstract: Introduction Human metabolism and inflammation are closely related modulators of homeostasis and immunity. Metabolic profiling is a useful tool to understand the association between metabolism and inflammation at a systemic level. Objective To investigate the longitudinal associations between the concentration of plasma metabolites and biomarkers related to inflammation and oxidative stress. Methods We conducted a repeated cross-sectional ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The metabolite 1-palmitoyl-GPI, was elevated in the cats with CaOx stones both as compared to cats with RD and cats with healthy kidneys. The elevation of 1-palmitoyl-GPI has been associated with an increased inflammatory condition in humans where it was correlated to the pro-inflammatory cytokine IL-8 (Gao et al, 2021 ) and was increased in the inflammation associated with periodontitis in mice (Ilievski et al, 2016 ). Increased concentrations of inflammatory glycosylphosphatidylinositols were observed in the cats eating the more inflammatory foods as compared to initial values or those cats eating a less inflammatory (high fish oil) food (Jewell & Jackson, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The metabolite 1-palmitoyl-GPI, was elevated in the cats with CaOx stones both as compared to cats with RD and cats with healthy kidneys. The elevation of 1-palmitoyl-GPI has been associated with an increased inflammatory condition in humans where it was correlated to the pro-inflammatory cytokine IL-8 (Gao et al, 2021 ) and was increased in the inflammation associated with periodontitis in mice (Ilievski et al, 2016 ). Increased concentrations of inflammatory glycosylphosphatidylinositols were observed in the cats eating the more inflammatory foods as compared to initial values or those cats eating a less inflammatory (high fish oil) food (Jewell & Jackson, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that immune system play an important role in pathophysiology of psychiatric disorders, involving altering immune cell and inflammatory cytokines, neurotransmitter metabolism, neuroendocrine function, neural plasticity, or reactive oxygen species ( 11 ). Inflammation is considered a central component of the innate immune response ( 12 ). Numerous studies have shown that many psychiatric disorders, such as depression and anxiety, are closely related to inflammation ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Histamine seems to have dualistic effects: (i) histamine, by way of activating pathways that promote the production of inflammatory mediators and cytokines, affects inflammation of the immune system, and (ii) the innate and adaptive immune responses are regulated by histamine [ 52 ]. Sarcosine, known to be part of the pathway of glycine, serine, and threonine metabolism, significantly associates with the levels of the inflammatory marker IL8 [ 53 ]. Intracellular accumulation of diacylglycerol, in muscle and liver, impairs insulin signaling by activating protein kinases C [ 54 ].…”
Section: Discussionmentioning
confidence: 99%